Hybrid Dynamic-Binary ALOHA Anti-Collision Protocol in RFID Systems - Kim, Jongwan (International Journal of Engineering and Technology, 2018)
The main techniques for identifying objects in an Internet of things environment are based on radio frequency identification, in which a specific object is identified by the reader through the tag mounted on the object. When there are multiple tags in the readerâ€™s interrogation zone, they respond simultaneously to the readerâ€™s request, thus causing a collision between the signals sent simultaneously to the reader from those tags. Such collisions reduce the data accuracy and prolong the identification time, thus making it difficult to provide a rapid service. This paper explores a hybrid anti-collision protocol, namely, the hybrid dynamic-binary ALOHA anti-collision protocol, which is designed to prevent tag collision and to enable more stable information transmission by improving the existing tag anti-collision protocols. The proposed protocol has achieved performance enhancement by shortening the tag identification process when tag collision occurs by combining the ALOHA and binary search protocols. In contrast to the existing protocols, whereby the readerâ€™s request is repeated after detecting a collision, the proposed protocol shortens the tag identification time by requesting only the collision bits. This contributes to a substantial reduction in the object identification time in an IoT environment.Â Â